Electrochemical Performance of Carbon/MnO2 Nanocomposites Prepared via Molecular Bridging as Supercapacitor Electrode Materials. Issue 5 (1st January 2015) - Ramirez-Castro, C.; Crosnier, O.; Athouël, L.; Retoux, R.; Bélanger, D.; Brousse, T.
Abstract : The chemical binding of amorphous manganese oxide and carbon particles was achieved with the diazonium chemistry. The synthesis was performed in two steps, with a first step consisting in the surface functionnalization of carbon particles with aminophenyl groups and the subsequent attachment of amorphous manganese oxide particles through generated phenyl groups. The bond between carbon and MnO2 particles is believed to occur between the carbon from the phenyl groups attached to carbon particles, and the oxygen atoms from the manganese oxide lattice. The capacitance of the carbon/MnO2 grafted nanocomposite electrode is doubled compared to a simple mixture of its two components. The capacitance of the nanocomposite electrode is also retained for faster cycling rates, thus highlighting the role of intimate coupling of carbon and MnO2 .